Endoscopies, blood‐borne viruses and blood donors: time to move on from precaution. Issue 3 (26th October 2020) - Hoad, Veronica C.; Serhan, George; Seed, Clive R.; Kiely, Philip; Gosbell, Iain B.
Abstract : Background and objectives: Based on the Council of Europe directive which dictates regulatory requirements in Australia, blood donors are currently deferred from donating for 4 months after an endoscopic procedure if either polyps were removed or a biopsy sample was taken. We aimed to assess the incidence of blood‐borne viruses (BBVs) (HIV, hepatitis B and C) in blood donors who donated after an endoscopic procedure and evaluate the risk to blood safety through risk modelling. Materials and methods: Donors from 1/1/2013 to 31/12/2017 with an endoscopy deferral on their blood donor file with pre‐ and post‐BBV testing were analysed to determine an incidence of BBVs using standard methods. The standard blood donor cohort was used as a comparator group. Using the incidence of endoscopies and BBV risk, the total residual risk estimate of allowing donors to return postendoscopy without restriction was calculated. Results: The incidence of a BBV postendoscopy in this large cohort of 16, 283 where testing has been confirmed postendoscopy was zero (95% CI 0–0·000105). The upper confidence interval of the zero events is 10·5 per 100 000 donations. Total positive donations from 2017 repeat donors were 1·87 per 100 000 (95% CI 0·0000117–0·0000277). Sensitivity analysis demonstrated that the residual risk remained negligible under realistic worst‐case scenarios. Conclusion: A BBV endoscopy deferral is not required for blood safety in Australia. The presented data has enabled us to submit a request for an exemption to our regulator, which has been approved and the policy change subsequently implemented by Lifeblood on 4/4/2020.